1999
DOI: 10.1016/s1055-3290(06)60345-2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Issues in HIV-Seropositive Women: A Survey Regarding Counseling, Contraception, Safer Sex, and Pregnancy Choices

Abstract: Sixty-nine HIV-seropositive women were surveyed with regard to the reproductive counseling they had received, contraception, safer sex practices, pregnancy histories, and pregnancy plans. Of the women surveyed, 84% and 90%, respectively, felt that they had access to the birth control and safer sex methods of their choice. Less than half felt that their physician had adequately counseled them about birth control. Women primarily cited social workers (46.4%) or nurses (34.8%) as the counseling source for birth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…10 In order to accomplish these objectives at best, medical interventions whether aiming at health promotion and disease prophylaxis or at the therapy of or rehabilitation from disease, should focus on specific demands of the target population they are designed for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In order to accomplish these objectives at best, medical interventions whether aiming at health promotion and disease prophylaxis or at the therapy of or rehabilitation from disease, should focus on specific demands of the target population they are designed for.…”
Section: Discussionmentioning
confidence: 99%
“…9,18,23 Periodic evaluation of women living with HIV/AIDS should include careful monitoring for evidence of disease progression, based on clinical manifestations and laboratory assessments of the degree of immune deficiency and viral replication. 10 This is best accomplished by means of determining CD4 1 cell counts and quantitative plasma viral loads and is considered essential for deciding whether to start patients on antiviral and prophylactic therapy or to change antiretrovirals in case of insufficient response. Access to such tests in the present cohort is concordant to national and international HIV/AIDS guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research is available regarding strategies of birth control counseling in HIV-positive women. Duggan et al (1999) reported on 69 seropositive women of childbearing age. Most of these women felt they had adequate access to safer sex protection of their choice, but their physicians were more likely to discuss safer sex issues than contraception.…”
Section: Conditions Associated With Hiv/aidsmentioning
confidence: 99%
“…(1995) found that although HIV infection does not affect reproductive decisions, mother’s health and vertical transmission risks do. Almost half of the women (48%) interviewed by Duggan et al . (1999) reported AZT information would affect future reproductive decisions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Kline et al (1995) found that although HIV infection does not affect reproductive decisions, mother's health and vertical transmission risks do. Almost half of the women (48%) interviewed by Duggan et al (1999) reported AZT information would affect future reproductive decisions. Vitiello and Smeltzer (1999) found a signi®cant relationship betweeǹ knowledge about AZT use during pregnancy and women's decision to consider pregnancy.'…”
Section: Review Of Literaturementioning
confidence: 99%